FISIP Duwe Gawe: Communication and Event Production - Restu Holiskya; Siti Khumayah; Aghnia Dian Lestari (Publikasi Indonesia, 2026)
Communication failures are common in events. Ineffective communication leads to the failure of an event. One student music concert that has survived for nine years is the Fisip Duwe Gawe Event, organized by the Student Executive Board (BEM-KM) of the Faculty of Social and Political Sciences of the University of Yogyakarta (UGJ) Cirebon. This study aims to examine the role of organizational communication and organizational culture in supporting the continuation of the Fisip Duwe Gawe event. A qualitative case study approach was used. Data were collected through interviews with several informants directly involved in the event's organization. Data analysis was conducted using source triangulation. The results of the study address the identified problem of how organizational communication and organizational culture exist within the Fisip Duwe Gawe event. Structured and participatory communication is one factor in the sustainability of the Fisip Duwe Gawe event, whose committee tends to change annually. The organizational culture within this event is also characterized by shared traditions and values passed down from generation to generation. Good communication and organizational culture within the Fisip Duwe Gawe event contribute to the event's survival and sustainability.